2019
DOI: 10.1109/access.2019.2923796
|View full text |Cite
|
Sign up to set email alerts
|

Improving Load Forecasting Process for a Power Distribution Network Using Hybrid AI and Deep Learning Algorithms

Abstract: Load forecasting is useful for various applications, including maintenance planning. The study of load forecasting using recent state-of-the-art hybrid artificial intelligence (AI) and deep learning (DL) techniques is limited in South Africa (SA) and South African power distribution networks. This paper proposes a novel hybrid AI and DL South African distribution network load forecasting system. The system comprises of modules that handle the collection of the loading data from the field, analysis of data inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…The SGTM neural-like structure showed a better prediction performance than MLR, SVR, and general regression neural networks. Motepe et al [ 17 ] developed an improved load forecasting process using hybrid AI and deep learning methods. They determined the optimal hyperparameters through several experiments to enhance the performance of long short-term memory (LSTM) networks.…”
Section: Related Studiesmentioning
confidence: 99%
“…The SGTM neural-like structure showed a better prediction performance than MLR, SVR, and general regression neural networks. Motepe et al [ 17 ] developed an improved load forecasting process using hybrid AI and deep learning methods. They determined the optimal hyperparameters through several experiments to enhance the performance of long short-term memory (LSTM) networks.…”
Section: Related Studiesmentioning
confidence: 99%
“…To mitigate this challenge and reduce the errors of the forecasting of the electric parameters, DBN is combined with Copula Model [27] and bidirectional Recurrent Neural Network [28], [29] for day and week ahead forecasting. An LSTM based hybrid DL method was tested by Motepe et al [30] for South African distribution network, showing an improved performance, considering the inclusion of temperature data. Deng et al [31] devised a deep multi-scale CNN (MSCNN) with time cognition and a selfdesigned time coding algorithm, which outperformed recursive multi-step LSTM, direct multi-step MSCNN and the direct multi-step gated CNN by MAPE of 34.73%, 14.22% and 19.05% respectively.…”
Section: ) Deep Learning (Dl)mentioning
confidence: 99%
“…WNN (Wavelet Neural Network) with BPNN has been used in MTLF to determine the reduction of the unavoidable stochastic part [41]. Neuro-fuzzy is a fuzzy logic-based ANN technique and has been applied to RNN, LSTM, ELM (Extreme Learning Machine) in STLF [91], and other ANNs for improving some issues in load forecasting. After reviewing 105 relevant deep learning-based load forecasting research works, it was found that STLF was the most important forecasting area, with 88 works on STLF.…”
Section: B Different Ann Techniques In Deep Learning Based Load Forementioning
confidence: 99%